Use of artificial intelligence in government control activities - Azevedo, Lauren de Almeida Barros; Albino, Jaqueline; Figueiredo, Josiel Maimone de (My University, 2022)
This exploratory research, limited to a bibliographic (scientific papers) and documentary (legisla-tion and institutional documents) survey, analyzed the adoption of artificial intelligence in government con-trol, based on the scientific production, identification of the tools in use, and the opportunities, challenges and strategies proposed by literature. A search was performed in the Web of Science database for scientific papers published as of 2015 using the descriptor artificial intelligence and government, which resulted in 272 papers analyzed by bibliometrics. Articles that could contribute to the discussion were then selected. The investigation showed the growth in scientific production, identified numerous tools, and reported the opportunities, challenges, and strategies suggested. In conclusion, using AI contributes significantly to gover-nment control, facilitating decision-making and risk prediction, and ensuring more effective actions, as long as ethical and legal issues are respected.
Keywords: Auditoria Interna; UNIDADE::SECRETARIA DE INTEGRIDADE PÚBLICA (SIP); artificial intelligence; government control; public procurement; ASSUNTO::Comunicação Social